2015
DOI: 10.1152/ajpendo.00098.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role of IGF-I in follistatin-induced skeletal muscle hypertrophy

Abstract: Follistatin, a physiological inhibitor of myostatin, induces a dramatic increase in skeletal muscle mass, requiring the type 1 IGF-I receptor/ Akt/mTOR pathway. The aim of the present study was to investigate the role of IGF-I and insulin, two ligands of the IGF-I receptor, in the follistatin hypertrophic action on skeletal muscle. In a first step, we showed that follistatin increases muscle mass while being associated with a downregulation of muscle IGF-I expression. In addition, follistatin retained its full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 70 publications
1
24
0
4
Order By: Relevance
“…Muscle atrophy is attributed to the imbalance of protein degradation and synthesis. There are two major signaling pathways controlling protein degradation, the ubiquitinproteasome (6)(7)(8)(9) and the autophagic lysosomal pathways (1). Both pathways are activated during muscle atrophy and contribute to the loss of muscle mass.…”
mentioning
confidence: 99%
“…Muscle atrophy is attributed to the imbalance of protein degradation and synthesis. There are two major signaling pathways controlling protein degradation, the ubiquitinproteasome (6)(7)(8)(9) and the autophagic lysosomal pathways (1). Both pathways are activated during muscle atrophy and contribute to the loss of muscle mass.…”
mentioning
confidence: 99%
“…Another important finding in the present study is the increased follistatin mRNA levels after AET. Previous studies have demonstrated a significant relationship between follistatin and muscle growth and/or hypertrophy . Actually, Sun et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a significant relationship between follistatin and muscle growth and/or hypertrophy. 59,60 Actually, Sun et al 11 showed that increased levels of mammalian target of rapamycin (mTOR) upregulate MyoD expression and microRNA-1 transcription, which suppresses HDAC4 and subsequently increases follistatin. This myogenic pathway mTOR/MyoD/microRNA-1/HDAC4/follistatin stimulates skeletal myoblast fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Um importante antagonista do TGFβ1 é a folistatina, que tem recebido crescente atenção devido aos seus potenciais efeitos terapêuticos sobre a perda de massa muscular (SEPULVEDA et al, 2015;CHEN et al, 2017) e, mais recentemente, a sensibilidade à ação da insulina no músculo esquelético (BARBE et al, 2015;BRANDT et al, 2015;HAN et al, 2019). Neste estudo, o exercício físico foi capaz de regular positivamente a expressão proteíca de folistatina, enquanto a cirurgia bariátrica não produziu o mesmo efeito.…”
Section: A Melhora Da Sensibilidade à Insulina No Músculo Esqueléticounclassified